Technical efficiency of wheat production among adopters and non-adopters of new technology in Fezzan Region, Libya - Alabasi, Hanan Ali Mohamed Ali (2018)
Wheat is considered the most valuable food in Libya and as the main staple food in Libyan diet. Libyan consumes a large quantity of wheat; the average consumed quantity about 145 kg/ capita. However, the current wheat production in Libya is just covers about 27% of the needs of the population, in which, almost about 1.6 million MT and the average yield about 1.25 MT/ha and this level is low comparing with the global wheat yield which is about 4.6 MT/ha. Although the efforts to enhance the productivity of wheat in Libya, it is still low and there is no improvement in wheat yield over the last decade indicating the usage of inputs in process of production is not efficient. Though some farms adopted new technology of planting wheat, nevertheless a lot of respondents are still using the old technology of production. Thereby, it is inevitable to assess the technical efficiency of wheat production in the areas in term of technology adoption in wheat planting. Therefore, this study aims to estimate the technical efficiency and resources used as well as determine the sources of technical inefficiency among wheat producers in south-western Libya. The study also aims to evaluate the economic performance of wheat producers by profitability analysis. Slack-based DEA model, fractional regression model as well as gross margin analysis applied in order to achieve the objectives of the study. The multistage cluster sampling method is used in order to select 225 respondents among adopters and non-adopters of new technology. The average technical efficiency for pooled sample farms is 76%, indicating that respondents can decrease their inputs on average by 24% and still produce the same level of output. Thereby, if all respondents work efficiently and have zero slack, input quantities can be reduced by 26.7%, 21.5%, 30.9%, 20.5,10.7% and 14.5% for DAP, seed, urea, organic fertilizers, size and labour. The average technical efficiency of non-adopters of new technology was 0.69 indicating that respondents were operating at a low level of technical efficiency while the mean efficiency estimated of adopters of new technology was 88%. Six (6) factors that show significant relationships with the inefficiency: the technology adoption, the age of respondents, main occupation, farm size, seed type and education. On the other hand, non- adopters of new technology can increase the profit by 24% by better use of inputs. The cost of seed and the cost of labour found to have a significant effect on profitability level of both groups. The study concluded that, respondents have a great chance to enhance their performance by adopting the new technology. The study recommended that improvement productivity programs should be targeted toward older farmers to improve their performance by training them in modern mechanization in agriculture. Moreover, the agriculture bodies should establish soil laboratory to enable the respondents to know the adequate quantity of fertilizer required. The government bodies should make facilities to help farmers to access and use the improved seed to improve the production.